THE EFFECT OF ZAKAT AS ONE OF THE PHILANTHROPY PRODUCTS ON THE INFLATION RATE IN INDONESIA FOR THE PERIOD OF 2015-2017 - Nabila Nabila; Sri Herianingrum (Universitas Airlangga, 2020)
This study aims to determine the effect of zakat on inflation in Indonesia in the period from January 2015 to December 2017. This study uses a quantitative approach with simple linear regression analysis. The collection of data in this study uses data on the amount of zakat for the period 2015 to 2017 that has been published by the National Zakat Agency (BAZNAS) and inflation rate data for the period of 2015 to 2017 obtained from the Central Statistics Agency (BPS). Based on the results of the study, the amount of zakat consisting of zakat maal and zakat fitrah collected by the BAZNAS has a significant effect on the inflation rate in Indonesia. This is because zakat will encourage consumption and investment and decrease wealth accumulation. Therefore, it will increase demand and inflation as well.Keywords: Zakat, Inflation, consumption, BAZNASREFFERENCE Ajija, Shochrul R dkk. (2011). Cara cerdas menguasai EViews. Jakarta: Salemba Empat.Andriyanto, I. (2014). Pemberdayaan zakat dalam meningkatkan kesejahteraan umat. Jurnal Zakat dan Wakaf, 1(2), 227-249 doi:http://dx.doi.org/10.21043/ziswaf.v1i2.1485Anggraini, R., Widiastuti, Tika. (2015). penyaluran dana zis dan tingkat inflasi berpengaruh terhadap pertumbuhan ekonomi indonesia priode 2011-2015. Jurnal Ekonomi Syariah Teori dan Terapan, 4(8), 630-641.Chaniago. (2015). Pemberdayaan zakat dalam mengentaskan kemiskinan. Jurnal Hukum Islam (JHI), 13(1), 47–56. https://doi.org/10.1126/science.aao0218Choudhury, M. A., & Rahman, A. N. M. A. (1993). Macroeconomic Relations in the Islamic Economic Order. International Journal of Social Economics, 13(6), 60-78.Kahf, M., & Al Yafai, S. (2015). Social security and zakāh in theory and practice. International Journal of Economics, 23(2), 189–215.Mansur, A. (2012). kebijakan fiskal dan implikasinya terhadap pembangunan. Journal of Islamic Economic and Business (JIEB), 02(1), 214–231.Mintarti, N. (2008). Zakat dan pembangunan : era baru zakat menuju kesejahteraan umat. Jakarta: Indonesia Magnificence of Zakat.Muhtada. (2014). Islamic philanthropy and the third sector. Islamika Indonesiana, 1(1), 106–123.Nidityo, Herwindo Ghora & Laila, N. (2014). Zakat produktif untuk meningkatkan kinerja produksi, motivasi dan religiusitas mustahiq. Jurnal Ekonomi Syariah Teori dan Terapan, 1(9), 661–673.Parakkasi, I. (2016). Inflasi dalam perspektif Islam. Laa Maisyir, 3(1), 41-58.Rahman, muhammad eka. (2016). Pengaruh zakat terhadap permintaan uang dalam Islam. Tesis tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Rasiam. (2014). Kebijakan fiskal dalam Islam (solusi bagi ketimpangan dan ketidakadilan distribusi). Jurnal Khatulistiwa, 4(1), 87–100. doi: https://doi.org/10.24260/khatulistiwa.v4i1.231Suseno, & Astiyah, S. (2009). Inflasi di Indonesia. Seri Kebanksentralan No. 22. Jakarta: Departemen Riset Kebanksentralan Bank Indonesia.Yusoff, M. B. (2006). Fiscal policy in an Islamic economyand the role of zakat. International Journal of Economics, Management and Accounting, 14(2), 1–23.